Reconceptualizing Exploitation: New Directions for an Old Concept in Social Stratification. (September 2015) - Avent-Holt, Dustin
Rent theory has taken off in stratification research, and a conceptualization of exploitation derived from rent theory has become popular in models of economic inequality. Some have argued that rent theory provides a more appropriate foundation for scientifically studying exploitation and economic inequality than neo-Marxian conceptualizations rooted in the labor theory of value. This article develops a critique of the rent-based conceptualization of exploitation, and two possible directions for reformulating the concept. I argue that rent-based exploitation fails to identify either a normatively or empirically defensible baseline condition that identifies when exploitation is absent and how much exists when it is present. To develop a more useful baseline, social scientists can either ground the concept in the normative worldviews of economic actors (positive approach) or in the normative commitments of the analyst himself or herself (normative approach). I use the social scientific literatures on distributive justice and fairness norms and the philosophical literature on exploitation and distributive justice to develop these alternatives, and conclude by discussing the strengths and weaknesses of each approach.